9(x+2)+6(x+6)=6x-6

Simple and best practice solution for 9(x+2)+6(x+6)=6x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+2)+6(x+6)=6x-6 equation:


Simplifying
9(x + 2) + 6(x + 6) = 6x + -6

Reorder the terms:
9(2 + x) + 6(x + 6) = 6x + -6
(2 * 9 + x * 9) + 6(x + 6) = 6x + -6
(18 + 9x) + 6(x + 6) = 6x + -6

Reorder the terms:
18 + 9x + 6(6 + x) = 6x + -6
18 + 9x + (6 * 6 + x * 6) = 6x + -6
18 + 9x + (36 + 6x) = 6x + -6

Reorder the terms:
18 + 36 + 9x + 6x = 6x + -6

Combine like terms: 18 + 36 = 54
54 + 9x + 6x = 6x + -6

Combine like terms: 9x + 6x = 15x
54 + 15x = 6x + -6

Reorder the terms:
54 + 15x = -6 + 6x

Solving
54 + 15x = -6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
54 + 15x + -6x = -6 + 6x + -6x

Combine like terms: 15x + -6x = 9x
54 + 9x = -6 + 6x + -6x

Combine like terms: 6x + -6x = 0
54 + 9x = -6 + 0
54 + 9x = -6

Add '-54' to each side of the equation.
54 + -54 + 9x = -6 + -54

Combine like terms: 54 + -54 = 0
0 + 9x = -6 + -54
9x = -6 + -54

Combine like terms: -6 + -54 = -60
9x = -60

Divide each side by '9'.
x = -6.666666667

Simplifying
x = -6.666666667

See similar equations:

| 71.80=25+0.15 | | 4y+3y=11 | | -x-3y=-23 | | x+4-3x^2=0 | | 3-2x+x=5x-5+2x | | 8w-32=4w | | -7-x=3x+17 | | 2x^2-50=24 | | 1x-4+1x=5(9-4x) | | 2-8x+1(x-4)=2(x-7) | | 6x+3=2x+31 | | m-14.6=9.74 | | 4+2x=5x-2 | | w-8=32 | | 4y-8=5y-1 | | 17dl=l | | 3x+4=-36-5x | | x=2*8+77 | | 16+5x= | | 3x+4=-35-5x | | (2x+5)x(7x-2)=(4x+3)x(5x-1)+82 | | 4(d-7)=524 | | X-4X+3Y+9Y-12=0 | | 5x+3x+120=360 | | 6*x*y-12=0 | | x+3x-4= | | f(x)=2x^4-3x | | y-1=-6/7(14) | | 3(2x+3)=45 | | (2x+5)=27 | | (x-5)10+(1-2x)15=(3-x)14 | | x-12y=-36 |

Equations solver categories